The Numerical Approaches to Heat Transfer Problem in Modern Electronic Structures - Raszkowski, Tomasz; Samson, Agnieszka (Computer Science, 2017)
The main aim of this paper is to present a detailed description of the research related to the modeling of heat conduction in modern electronic structures including special consideration of numerical aspects of analyzed algorithms.The motivation to undertake the research and some most important results of experiments and simulations are also included. Moreover, the numerical appoximation of the problem as well as the methodology and the sample solution of mentioned problem are presented. In the main part, the discretisation techniques, Ordinary Differential Equation algorithms and simulation results for Runge-Kutta and Gear’s algorithms are analysed and discussed. Additionally, a new effective approach to modelling of heat transfer in electronic nanostructures is demonstrated.